2019
DOI: 10.1186/s42490-019-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

A high content, phenotypic ‘scar-in-a-jar’ assay for rapid quantification of collagen fibrillogenesis using disease-derived pulmonary fibroblasts

Abstract: Background: Excessive extracellular matrix (ECM) deposition is a hallmark feature in fibrosis and tissue remodelling diseases. Typically, mesenchymal cells will produce collagens under standard 2D cell culture conditions, however these do not assemble into fibrils. Existing assays for measuring ECM production are often low throughput and not disease relevant. Here we describe a robust, high content, pseudo-3D phenotypic assay to quantify mature fibrillar collagen deposition which is both physiologically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Currently, many in vitro models only allow investigations of fibrogenesis in acute studies of 1-3 days [28,34] although some models extend to a few weeks [44]. To our knowledge, this is the first time that a 12 days fibroblast culture has been combined with the investigation of ECM synthesis in the supernatant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many in vitro models only allow investigations of fibrogenesis in acute studies of 1-3 days [28,34] although some models extend to a few weeks [44]. To our knowledge, this is the first time that a 12 days fibroblast culture has been combined with the investigation of ECM synthesis in the supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the addition of a crowding agent induced complete cleavage of the type I collagen C-propeptide, whereas the fibroblasts in the non-crowded culture conditions continued to secrete intact procollagen. Recently, Good et al described a 72 h high content screening Scar-in-a-Jar assay utilizing fibroblasts from IPF patients, that allowed the quantification of disease-relevant ECM deposition in vitro [34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3D cell cultures can be used to more closely mimic the organization of skin as a tissue structure. Such "scar in a jar" models are likely to be useful moving forward [126]. It has also been suggested that media components may be altered to create a pseudo "crowded" environment in culture.…”
Section: Cellularmentioning
confidence: 99%
“…[ 157 ] A similar study, combined macromolecular crowding with TGF‐β to develop a robust, high throughput, phenotypic screening assay using pulmonary fibroblasts derived from patients affected by idiopathic pulmonary fibrosis. [ 158 ] The Scar‐in‐a‐Jar offers a novel pathophysiologically relevant screening and evaluation tool for antifibrotic compounds interfering with different key steps in the collagen biosynthesis pathway.…”
Section: Biophysical Cuesmentioning
confidence: 99%